-(5y+5)-(-4y-6)=-3

Simple and best practice solution for -(5y+5)-(-4y-6)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5y+5)-(-4y-6)=-3 equation:


Simplifying
-1(5y + 5) + -1(-4y + -6) = -3

Reorder the terms:
-1(5 + 5y) + -1(-4y + -6) = -3
(5 * -1 + 5y * -1) + -1(-4y + -6) = -3
(-5 + -5y) + -1(-4y + -6) = -3

Reorder the terms:
-5 + -5y + -1(-6 + -4y) = -3
-5 + -5y + (-6 * -1 + -4y * -1) = -3
-5 + -5y + (6 + 4y) = -3

Reorder the terms:
-5 + 6 + -5y + 4y = -3

Combine like terms: -5 + 6 = 1
1 + -5y + 4y = -3

Combine like terms: -5y + 4y = -1y
1 + -1y = -3

Solving
1 + -1y = -3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -1y = -3 + -1

Combine like terms: 1 + -1 = 0
0 + -1y = -3 + -1
-1y = -3 + -1

Combine like terms: -3 + -1 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| 7.3x-8=6.3x+1 | | y/20=-26 | | 3(2x-1)+5=13 | | a=1/2(18*24) | | 1/6x=39 | | 17-3x=2x-2 | | 786=x+34+4(x-40) | | 8x5/9 | | -4(2b+3)+(9b-7)=0 | | 5(4x-6)-19x=7 | | 4x+1=2(x-7) | | b+8b-22=0 | | 3.5q-3.7-5.8q=-3.3q-3.9 | | 6y+5=5y-3 | | (21/25)(10/117)(27/14) | | 13-2/3x=3 | | 384-1/12 | | (8m-8m-27)(8m-25m-14)=0 | | .3(y)+.14(x)=.18 | | x+4x=58 | | -(3/5)x=(2/5) | | F(9)=100x-5 | | 5x/6-y/3=6 | | 19m=40-17.95 | | 36m^2-49/16=0 | | 37=-2(22-X)+3(X-3) | | (9-3x)(9-5x)= | | -11x^2+3x+11=0 | | 382=x+(x+6) | | (4/11)x=28 | | 3x-108=0 | | 7k-4k=12 |

Equations solver categories